2009
DOI: 10.1080/15368370902918912
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mobile-Phone Electromagnetic Fields on Brain Electrical Activity: A Critical Analysis of the Literature

Abstract: We analyzed the reports in which human brain electrical activity was compared between the presence and absence of radio-frequency and low-frequency electromagnetic fields (EMFs) from mobile phones, or between pre- and post-exposure to the EMFs. Of 55 reports, 37 claimed and 18 denied an EMF-induced effect on either the baseline electro encephalogram (EEG), or on cognitive processing of visual or auditory stimuli as reflected in changes in event-related potentials. The positive reports did not adequately consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 84 publications
(185 reference statements)
0
14
0
Order By: Relevance
“…The growing use of mobile phones (MPs) has driven neuroscientists to focus their attention on the potential impact of this technology on human health [1] and brain functions [2]. Aninteraction between electromagnetic fields (EMFs) due to radiofrequency and cerebral activity could be hypothesized, given the fair amount of radiofrequency emitted by mobile phones absorbed by the skull and reaching the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The growing use of mobile phones (MPs) has driven neuroscientists to focus their attention on the potential impact of this technology on human health [1] and brain functions [2]. Aninteraction between electromagnetic fields (EMFs) due to radiofrequency and cerebral activity could be hypothesized, given the fair amount of radiofrequency emitted by mobile phones absorbed by the skull and reaching the brain.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other evidence was not able to show that acute exposure to the GSM-EMFs could induce measurable biological effects on brain functioning in rest condition (Krause et al, 2000a). To complicate the picture, it has been suggested a possible effect of an unconscious conditioning on experiments' mind on the basis of the expectations of the donors (Marino and Carrubba, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…EMFs have been shown to damage the blood–brain barrier,5 increase oxidative stress6 and induce apoptosis7 in the human brain. In experimental laboratory settings, studies have shown significant effects of mobile radiation on epilepsy 8. However, real-world clinical studies to understand the role of mobile usage on epilepsy are scarce.…”
Section: Introductionmentioning
confidence: 99%